Patent foramen ovale revealed by COVID-19 pneumonia - Vanhomwegen, Charlotte; Taton, Olivier; Selvais, Nicolas; Vanhove, Olivier; Leduc, Dimitri (BMC pulmonary medicine, 2021)
Platypnea-orthodeoxia syndrome (POS) is a rare condition characterized by dyspnoea (platypnea) and arterial desaturation in the upright position resolved in the supine position (orthodeoxia). Intracardiac shunt, pulmonary ventilation-perfusion mismatch and others intrapulmonary abnormalities are involved. We report a case of POS associated with two pathophysiological issues: one, cardiac POS caused by a patent foramen ovale (PFO) and second, pulmonary POS due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) interstitial pneumonia. POS has resolved after recovery of coronavirus disease 2019 (COVID-19) pneumonia. Right-to-left interatrial shunt and intrapulmonary shunt caused by SARS-CoV-2 pneumonia contributed to refractory hypoxemia and POS. Therefore, in case of COVID-19 patient with unexplained POS, the existence of PFO must be investigated.